2022
DOI: 10.1002/14651858.cd010452.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of enteric fever (typhoid and paratyphoid fever) with cephalosporins

Abstract: Background Typhoid and paratyphoid (enteric fever) are febrile bacterial illnesses common in many low‐ and middle‐income countries. The World Health Organization (WHO) currently recommends treatment with azithromycin, ciprofloxacin, or ceftriaxone due to widespread resistance to older, first‐line antimicrobials. Resistance patterns vary in different locations and are changing over time. Fluoroquinolone resistance in South Asia often precludes the use of ciprofloxacin. Extensively drug‐resistant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 98 publications
0
2
0
Order By: Relevance
“…et al (2021) reported that the combination of Azithromycin with other antibiotics led to a quicker resolution of symptoms and a shorter hospital stay (22). Their findings suggested that Azithromycin could play a vital role in enhancing the effectiveness of the treatment for enteric fever (23,24). However, it is essential to observe that the variations in findings could be attributed to differences in study populations, antibiotic resistance patterns, and the strains of pathogens involved.…”
Section: Discussionmentioning
confidence: 99%
“…et al (2021) reported that the combination of Azithromycin with other antibiotics led to a quicker resolution of symptoms and a shorter hospital stay (22). Their findings suggested that Azithromycin could play a vital role in enhancing the effectiveness of the treatment for enteric fever (23,24). However, it is essential to observe that the variations in findings could be attributed to differences in study populations, antibiotic resistance patterns, and the strains of pathogens involved.…”
Section: Discussionmentioning
confidence: 99%
“…Data derived from a study in Nigeria indicate that oral ciprofloxacin for Salmonella bacteremia seems to be a common practice [28]. Patients receiving ciprofloxacin may have lower rates of microbiological failure and relapse compared to cefixime [29]. However, in a randomized trial from Pakistan, cefixime was as effective as ceftriaxone for bacteremic typhoid fever; more than 8-day treatment may not provide any additional benefit [30,31].…”
Section: Effect Of Acute Febrile Infection On Oral Antibiotic Absorptionmentioning
confidence: 99%
“…Internal bleeding, bronchitis, pneumonia, and other respiratory issues, inflammation of the heart, inflammation of the bones (osteomyelitis), kidney failure, a swollen or burst gallbladder, intestinal perforation (a hole in the intestine), swelling around the brain (meningitis), neurological (brain) symptoms, and miscarriage are all complications of typhoid fever if it is not treated immediately. [88].…”
Section: Signs and Symptoms Of Typhoid Fevermentioning
confidence: 99%